Pengaruh Model Pembelajaran PBL (Project Based Learning) pada Materi Pendudukan Jepang di Indonesia terhadap Kemampuan Berpikir Kritis Siswa Kelas XI MIPA di SMA Negeri 1 Pagaden Kabupaten Subang - Sari, Devi Novita; Ribawati, Eko; Maryuni, Yuni (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of the application of the project based learning model in Indonesian history subjects on the material of the Japanese occupation in Indonesia on the critical thinking skills of XI MIPA class students at SMA Negeri 1 Pagaden in Subang. The method used in this research is quasi-experimental method using pretest-posttest control group design. The sampling technique in this study was purposive sample with XI MIPA 1 class of 34 students as experimental class using project based learning model and XI MIPA 2 class of 33 students as control class using discovery learning model. Based on the results of data analysis, it is obtained that there is an effect of using the project based learning model on the material of the Japanese occupation in Indonesia on students' critical thinking skills. Based on the results of the t test analysis, the tcount value of 4.42 is not equal to ttable value of 1.67 with a significance level of 0.05, so Ho is rejected and H1 is accepted, so there is an effect of the application of the project based learning model on the material of the Japanese occupation in Indonesia on the critical thinking skills of XI MIPA class students at SMA Negeri 1 Pagaden in Subang. Keywords: Project Based Learning Model, History Learning, Critical Thinking Skills